Perception of Street Vendors and Management by Kathmandu Metropolitan City (Samriddhi Journal of Development Studies, 2023)
This paper delves into the recent eviction of street vendors by the Kathmandu Metropolitan City (KMC) aimed at ensuring pedestrian mobility rights. The eviction has raised concerns about the livelihoods of street vendors, prompting an exploration of various stakeholder viewpoints. Drawing on Key Informant Interviews and interviews, this research sheds light on the complex interplay of perspectives. Street vendors express satisfaction with the KMC’s effort to clear the roads, yet show apprehension about their compromised livelihoods due to a lack of alternatives. Pedestrians support KMC’s endeavor, acknowledging an enhanced right to unobstructed movement, while expressing empathy for the vendors’ economic struggles. The Nepal Street Vendor Trade Union (NEST) criticizes KMC’s approach and advocates for alternatives that safeguards the vendor’s right to livelihood. KMC justifies its eviction measures as essential for pedestrians’ right to mobility through efficient road management. The study underscores the need for collaborative and communicative efforts among stakeholders to effectively manage the street vendors.